Nutrition of Florida Citrus Trees, Second Edition - Thomas A. Obreza; Kelly T. Morgan (EDIS, 2008)
Revised! SL-253, a 100-page illustrated handbook edited by Thomas A. Obreza and Kelly T. Morgan, updates and expands upon the first edition (SP-169) including new information and updated recommendations crystallized from more than 60 citrus research and extension publications produced by UF/IFAS faculty since the first edition was published in 1995. It provides background information and recommendations to develop a sound citrus nutrition program that optimizes financial returns while sustaining yields and maintaining soil and water quality. Published by the UF Soil and Water Sciences Department, January 2008.